The Null Result Penalty - Felix Chopra; Ingar K. Haaland; Christopher Roth; Andreas Stegmann (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine how the evaluation of research studies in economics depends on whether a study yielded a null result. Studies with null results are perceived to be less publishable, of lower quality, less important, and less precisely estimated than studies with significant results, even when holding constant all other study features, including the precision of estimates. The null result penalty is of similar magnitude among PhD students and journal editors. The penalty is larger when experts predict a large effect and when statistical uncertainty is communicated with p-values rather than standard errors. Our findings highlight the value of pre-results review.
Keywords: 330; null results; publication bias; learning; information; scientific communication